Functional characterization of dopamine and norepinephrine transport across the apical and basal plasma membranes of the human placental syncytiotrophoblast - Horackova, Hana; Karahoda, Rona; Vachalova, Veronika; Turkova, Helena; Abad, Cilia; Staud, Frantisek (Scientific reports, 2022)
The human placenta represents a unique non-neuronal site of monoamine transporter expression, with pathophysiological relevance during the prenatal period. Monoamines (serotonin, dopamine, norepinephrine) are crucial neuromodulators for proper placenta functions and fetal development, including cell proliferation, differentiation, and neuronal migration. Accumulating evidence suggests that even a transient disruption of monoamine balance during gestation may lead to permanent changes in the fetal brain structures and functions, projecting into adulthood. Nonetheless, little is known about the transfer of dopamine and norepinephrine across the placental syncytiotrophoblast. Employing the method of isolated membranes from the human term placenta, here we delineate the transport mechanisms involved in dopamine and norepinephrine passage across the apical microvillous (MVM) and basal membranes. We show that the placental uptake of dopamine and norepinephrine across the mother-facing MVM is mediated via the high-affinity and low-capacity serotonin (SERT/SLC6A4) and norepinephrine (NET/SLC6A2) transporters. In the fetus-facing basal membrane, however, the placental uptake of both monoamines is controlled by the organic cation transporter 3 (OCT3/SLC22A3). Our findings thus provide insights into physiological aspects of dopamine and norepinephrine transport across both the maternal and fetal sides of the placenta. As monoamine transporters represent targets for several neuroactive drugs such as antidepressants, our findings are pharmacologically relevant to ensure the safety of drug use during pregnancy.
Keywords: Trophoblasts; serotonin; Pregnancy; noradrenalin; těhotenství; Norepinephrine; Adult; Placenta; trofoblasty; dospělí; dopamin; Dopamine; membránové transportní proteiny pro serotonin; Cell Membrane; placenta; lidé; ženské pohlaví; Serotonin Plasma Membrane Transport Proteins; Humans; buněčná membrána; Female; Serotonin